Systematic Review of Linezolid Population Pharmacokinetics in Pediatric: Models, Covariates, and Dosing Implication - Primasari, Firdhani Satia; Hakim, Arief Rahman (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2025)
Background: The increasing prevalence of bacterial resistance has positioned linezolid as a promising antibiotic for treating infections, including in pediatric patients. Knowledge of pharmacokinetic parameters is very useful in optimizing the dose to be used in patient therapy. However, pharmacokinetic data to guide optimized dosing in children remain limited.Objectives: This review aims to summarize population pharmacokinetic (PopPK) models of linezolid in pediatric populations and identify significant covariates influencing its pharmacokinetics.Methods: A systematic search was conducted in PubMed and ScienceDirect databases for studies published between 2014 and May 2025 using the keywords "linezolid", "population pharmacokinetics", and "pharmacokinetic model".Results: Six studies met the inclusion criteria and were analysed. The pharmacokinetic models were mainly based on blood concentration measurements and constructed using NONMEM in four studies. Most studies employed one-compartment models. Clearance values ranged from 0.068 to 5.82 L/h, and volume of distribution from 0.783 to 10.5 L. Body weight consistently emerged as a significant predictor of clearance, while body surface area was associated with volume of distribution.Conclusion: PopPK modeling highlights considerable variability in linezolid pharmacokinetics among pediatric patients, influenced primarily by weight and other covariates. Further studies are needed to compare oral versus IV formulations and to incorporate unbound (free) drug concentrations for improved dose optimization in pediatric populations.